TERRORISM IMPACT ON INSURANCE INDUSTRY - Liviu UZLAU (Hyperion Economic Journal, 2015)
Terrorism is a more and more discussed topic. All over the world common people and experts talk about victims, casualties and physical damage. What about economic effects? Not only in terms of costs, but also regarding how terrorist acts affect different branches of the economy. Before 2001, September 11th insurance industry did not think about taking into consideration terrorist risk and assess them accordingly. In financial terms, does this industry gain or lose? In the following work a few issues regarding these questions might be answered.